ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DITINJAU DARI SELF-EFFICACY SISWA - Lusi Erlina; Moh Zayyadi; Chairul Fajar Tafrilyanto (Almeera Education, 2025)
This study aims to describe students’ mathematical problem-solving abilities based on their levels of self-efficacy using the IDEAL Problem Solving steps. This descriptive qualitative research was conducted at SMPN 1 Pademawu with five purposively selected students representing very high to very low self-efficacy categories. The instruments used included a self-efficacy questionnaire, problem-solving tests, and interviews. The results show that higher self-efficacy is associated with better performance in understanding problems, selecting strategies, performing calculations, and evaluating solutions, while students with low self-efficacy experience difficulties in nearly all IDEAL stages.